High-water filling material as well as preparation method and application thereof
By mixing cement, fly ash, coal gangue, bentonite, white carbon black and admixtures in a specific proportion in high-water filling materials and combining them with alkaline exciter solutions, the problem of insufficient strength of existing high-water filling materials is solved, and higher compressive strength and filling effect are achieved.
Patent Information
- Application Number
- CN202411845156.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-13
- Publication Date
- 2025-03-28
AI Technical Summary
The strength of existing high-water filling materials is relatively average and cannot effectively fill spaces such as underground goafs and mine tunnels.
High water-filled materials with higher strength are prepared by mixing cement, fly ash, gangue, bentonite, white carbon black and admixtures in a specific proportion and combining with alkaline exciter solution.
The compressive strength of high-water filling materials is improved, so that their compressive strength of 28d reaches more than 25MPa, meeting the needs of filling underground goafs and mine tunnels.
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of filling materials, and in particular relates to a high-water filling material and a preparation method and application thereof. Background Art
[0002] High-water filling material is a filling material with a very high water-cement ratio. It can form a filling body with a certain strength under high water content. It is mainly used to fill underground goafs, mine tunnels and other spaces.
[0003] High water filling materials are generally composed of gelling materials, filling materials, additives and water. However, the strength of high water filling materials prepared in the prior art is relatively general, so they cannot play a good filling role. Therefore, a high water filling material with higher strength is urgently needed. Summary of the invention
[0004] The purpose of the present invention is to provide a high water filling material and a preparation method and application thereof. The high water filling material provided by the present invention has better strength.
[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0006] The present invention provides a high-water filling material, comprising a cementitious material and water; the cementitious material comprises the following components in parts by weight: 10 parts of cement, 5-20 parts of fly ash, 20-40 parts of coal gangue, 0.1-0.5 parts of alkali activator, 1-10 parts of bentonite, 1-10 parts of white carbon black and 0.01-0.5 parts of an admixture; the mass ratio of the water to the cementitious material is 2-15:1.
[0007] Preferably, the coal gangue has continuous grading; the mass percentages of the various gradings are: 40-60% of 0-6 mm coal gangue, 10-30% of 6-8 mm coal gangue and 10-30% of 8-12 mm coal gangue.
[0008] Preferably, the alkaline activator includes one or more of sodium hydroxide, potassium hydroxide, water glass and sodium aluminate.
[0009] Preferably, the admixture includes one or more of a retarder, a water reducing agent, a defoaming agent and a water retaining agent.
[0010] Preferably, the particle size of the fly ash is less than 45 μm.
[0011] Preferably, the particle size of the bentonite is less than 25 μm.
[0012] Preferably, the particle size of the white carbon black is 10 to 800 nm.
[0013] Preferably, the mass ratio of water to gelling material is 2 to 10:1.
[0014] The present invention also provides a method for preparing the high water filling material described in the above technical solution, comprising the following steps:
[0015] (1) mixing cement, fly ash, coal gangue, bentonite, white carbon black and an admixture to obtain a mixture;
[0016] (2) mixing an alkali activator and water to obtain an alkali activator solution;
[0017] (3) mixing the mixture obtained in step (1) and the alkaline activator solution obtained in step (2) to obtain a high water filling material;
[0018] There is no order of precedence for steps (1) and (2).
[0019] The present invention also provides the use of the high-water filling material described in the above technical solution or the high-water filling material prepared according to the preparation method described in the above technical solution in underground coal mines.
[0020] The present invention provides a high-water filling material, including a cementitious material and water; the cementitious material includes the following components by weight: 10 parts of cement, 5-20 parts of fly ash, 20-40 parts of coal gangue, 0.1-0.5 parts of alkali activator, 1-10 parts of bentonite, 1-10 parts of white carbon black and 0.01-0.5 parts of admixture; the mass ratio of water to cementitious material is 2-15:1. The bentonite and white carbon black in the present invention have a synergistic effect to improve the compressive strength of the filling material; the composition of the filling material and the amount of each component are controlled, and the components cooperate to make the high-water filling material have excellent compressive strength. The results of the embodiment show that the 28d compressive strength of the high-water filling material provided by the present invention is above 25MPa. DETAILED DESCRIPTION
[0021] The present invention provides a high-water filling material, comprising a cementitious material and water; the cementitious material comprises the following components in parts by weight: 10 parts of cement, 5-20 parts of fly ash, 20-40 parts of coal gangue, 0.1-0.5 parts of alkali activator, 1-10 parts of bentonite, 1-10 parts of white carbon black and 0.01-0.5 parts of an admixture; the mass ratio of the water to the cementitious material is 2-15:1.
[0022] Unless otherwise specified, the present invention has no particular limitation on the sources of the components, and commercially available products known to those skilled in the art may be used.
[0023] The high water filling material provided by the present invention comprises a gelling material.
[0024] The cementitious material provided by the present invention includes 10 parts of cement by weight. In the present invention, the cement undergoes a hydration reaction to form a gel product, which can bond other solid particles together to improve the strength of the filling material.
[0025] The present invention has no particular limitation on the type of cement, and cements well known to those skilled in the art can be used. In an embodiment of the present invention, the cement is ordinary Portland cement PO 42.5.
[0026] Based on 10 parts of cement, the cementitious material provided by the present invention includes 5 to 20 parts of fly ash. In an embodiment of the present invention, the amount of fly ash can be specifically 5 parts, 8 parts, 10 parts, 12 parts, 14 parts, 16 parts, 18 parts or 20 parts. In the present invention, the fly ash has a volcanic ash effect, and the components such as active silica therein can undergo a volcanic ash reaction to improve the strength of the filling material, and can be filled in the gaps in the filling material to further improve the strength of the filling material and make the filling material have better fluidity.
[0027] In the present invention, the particle size of the fly ash is preferably less than 45 μm, more preferably 5 to 45 μm. The present invention controls the amount and particle size of the fly ash within the above range, which can further improve the strength of the filling material.
[0028] Based on 10 parts of cement, the cementitious material provided by the present invention includes 20 to 40 parts of coal gangue. In an embodiment of the present invention, the amount of the coal gangue can be specifically 20 parts, 25 parts, 30 parts, 35 parts or 40 parts. In the present invention, the coal gangue plays a role as a skeleton, and some active ingredients therein can react to form a cementitious substance to improve the strength of the filling material.
[0029] In the present invention, the coal gangue preferably has a continuous gradation; the mass percentage of each gradation is preferably: 40-60% of 0-6mm coal gangue, 10-30% of 6-8mm coal gangue and 10-30% of 8-12mm coal gangue, and more preferably: 42-58% of 0-6mm coal gangue, 12-28% of 6-8mm coal gangue and 12-28% of 8-12mm coal gangue. The present invention uses coal gangue with a continuous gradation and controls the mass percentage of each gradation to improve the density of the filling material and further improve the mechanical strength of the filling material.
[0030] Based on 10 parts of cement, the cementitious material provided by the present invention includes 0.1 to 0.5 parts of alkali activator. In an embodiment of the present invention, the amount of the alkali activator can be specifically 0.1 part, 0.2 part, 0.3 part, 0.4 part or 0.5 part.
[0031] In the present invention, the alkaline activator preferably includes one or more of sodium hydroxide, potassium hydroxide, water glass and sodium aluminate. The present invention controls the amount and type of the alkaline activator within the above range, which can further improve the mechanical strength of the filling material.
[0032] Based on 10 parts of cement, the cementitious material provided by the present invention includes 1 to 10 parts of bentonite. In an embodiment of the present invention, the amount of bentonite can be specifically 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.
[0033] In the present invention, the bentonite is preferably organic bentonite; the particle size of the bentonite is preferably less than 25 μm, more preferably 1 to 25 μm. In the present invention, the bentonite has good suspension and thixotropy, can increase the viscosity of the slurry, improve its fluidity, react with cement and the like and fill the pores, and has a synergistic effect with white carbon black, thereby improving the mechanical strength of the filling material. The present invention controls the amount and particle size of the bentonite within the above range, which can further improve the mechanical strength of the filling material.
[0034] Based on 10 parts of cement, the cementitious material provided by the present invention includes 1 to 10 parts of white carbon black. In an embodiment of the present invention, the amount of white carbon black can be specifically 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, 7 parts, 8 parts, 9 parts or 10 parts.
[0035] In the present invention, the white carbon black is preferably fumed silica; the particle size of the white carbon black is preferably 10 to 800 nm. In the present invention, the white carbon black and bentonite have a synergistic effect, thereby improving the mechanical strength of the filling material. The present invention controls the amount, type and particle size of the white carbon black within the above range, which can further improve the mechanical properties of the filling material.
[0036] Based on 10 parts of cement, the cementitious material provided by the present invention includes 0.01 to 0.5 parts of admixture. In an embodiment of the present invention, the amount of the admixture can be specifically 0.01 parts, 0.05 parts, 0.1 parts, 0.2 parts, 0.3 parts, 0.4 parts or 0.5 parts.
[0037] In the present invention, the admixture preferably includes one or more of a retarder, a water reducing agent, a defoaming agent and a water retaining agent.
[0038] In the present invention, the retarder preferably includes one or more of sodium citrate, borax and phosphate.
[0039] In the present invention, the water reducer is preferably a polycarboxylic acid high-efficiency water reducer.
[0040] In the present invention, the defoamer preferably includes one or more of an organosilicon defoamer and a polyether defoamer.
[0041] In the present invention, the water retaining agent preferably includes one or more of polyacrylamide and sodium polyacrylate.
[0042] The present invention has no particular limitation on the source of the admixture, and commercially available products known to those skilled in the art may be used.
[0043] The high-water filling material provided by the present invention also includes water.
[0044] In the present invention, the mass ratio of water to gelling material is preferably 2 to 15: 1, more preferably 2 to 10: 1. The present invention controls the mass ratio of water to gelling material within the above range, which can make the high-water filling material have better fluidity, easier to pump into the required filling area, and at the same time make the filling material have excellent mechanical strength.
[0045] The bentonite and white carbon black in the present invention have a synergistic effect to improve the compressive strength of the filling material; the composition of the filling material and the amount of each component are controlled, and the components cooperate to make the high-water filling material have excellent compressive strength.
[0046] The present invention also provides a method for preparing the high water filling material described in the above technical solution, comprising the following steps:
[0047] (1) mixing cement, fly ash, coal gangue, bentonite, white carbon black and an admixture to obtain a mixture;
[0048] (2) mixing an alkali activator and water to obtain an alkali activator solution;
[0049] (3) mixing the mixture obtained in step (1) and the alkaline activator solution obtained in step (2) to obtain a high water filling material;
[0050] There is no order of precedence for steps (1) and (2).
[0051] The invention mixes cement, fly ash, coal gangue, bentonite, white carbon black and an additive to obtain a mixture.
[0052] The present invention has no special limitation on the mixing operation of the cement, fly ash, coal gangue, bentonite, white carbon black and admixtures. The components can be uniformly mixed using a material mixing technical scheme well known to those skilled in the art.
[0053] The invention mixes the alkali activator and water to obtain the alkali activator solution.
[0054] The present invention has no special limitation on the mixing operation of the alkaline activator and water, and the two can be mixed evenly using a material mixing technical solution well known to those skilled in the art.
[0055] After obtaining the mixture and the alkaline activator solution, the present invention mixes the mixture and the alkaline activator solution to obtain a high water filling material.
[0056] The present invention has no special limitation on the mixing operation of the mixture and the alkaline activator solution, and the two can be mixed evenly using a material mixing technical solution well known to those skilled in the art.
[0057] The present invention also provides the use of the high-water filling material described in the above technical solution or the high-water filling material prepared according to the preparation method described in the above technical solution in underground coal mines.
[0058] The present invention has no special limitation on the operation of the application, and the technical solutions of the application well known to those skilled in the art may be adopted.
[0059] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0060] Example 1
[0061] A high-water filling material, composed of a cementitious material and water; the cementitious material is composed of the following components by weight: 10 parts of cement (ordinary Portland cement PO 42.5), 10 parts of fly ash (5-45 μm), 20 parts of coal gangue (with continuous grading; the mass percentage of each grade is: 52% of 0-6 mm coal gangue, 25% of 6-8 mm coal gangue and 23% of 8-12 mm coal gangue), 0.1 part of alkali activator (sodium hydroxide), 2 parts of bentonite (organic bentonite, 1-25 μm), 2 parts of white carbon black (fumed silica, 10-500 nm) and 0.2 parts of admixture (0.1 part of polycarboxylic acid high-efficiency water reducing agent, 0.1 part of borax); the mass ratio of water to cementitious material is 3:1;
[0062] The high water filling material is prepared by: (1) mixing cement, fly ash, coal gangue, bentonite, white carbon black and an admixture to obtain a mixture;
[0063] (2) mixing an alkali activator and water to obtain an alkali activator solution;
[0064] (3) Mixing the mixture obtained in step (1) and the alkaline activator solution obtained in step (2) to obtain a high water filling material.
[0065] Example 2
[0066] A high-water filling material, composed of a cementitious material and water; the cementitious material is composed of the following components by weight: 10 parts of cement (ordinary Portland cement PO 42.5), 15 parts of fly ash (5-45 μm), 30 parts of coal gangue (with continuous grading; the mass percentage of each grade is: 52% of 0-6 mm coal gangue, 25% of 6-8 mm coal gangue and 23% of 8-12 mm coal gangue), 0.15 parts of alkali activator (sodium hydroxide), 5 parts of bentonite (organic bentonite, 1-25 μm), 5 parts of white carbon black (fumed silica, 10-500 nm) and 0.3 parts of admixture (0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.1 parts of borax); the mass ratio of water to cementitious material is 3:1;
[0067] The preparation method of the high water filling material is the same as that of Example 1.
[0068] Example 3
[0069] A high-water filling material, composed of a cementitious material and water; the cementitious material is composed of the following components by weight: 10 parts of cement (ordinary Portland cement PO 42.5), 20 parts of fly ash (5-45 μm), 35 parts of coal gangue (with continuous grading; the mass percentage of each grade is: 52% of 0-6 mm coal gangue, 25% of 6-8 mm coal gangue and 23% of 8-12 mm coal gangue), 0.15 parts of alkali activator (sodium hydroxide), 8 parts of bentonite (organic bentonite, 1-25 μm), 5 parts of white carbon black (fumed silica, 10-500 nm) and 0.3 parts of admixture (0.2 parts of polycarboxylic acid high-efficiency water reducing agent, 0.1 parts of borax); the mass ratio of water to cementitious material is 3:1;
[0070] The preparation method of the high water filling material is the same as that of Example 1.
[0071] Example 4
[0072] The gradation percentages of the coal gangue in Example 3 are replaced by: 58% of 0-6 mm coal gangue, 12% of 6-8 mm coal gangue and 30% of 8-12 mm coal gangue. Other parameters are the same as those in Example 3.
[0073] Comparative Example 1
[0074] The white carbon black in Example 3 was omitted, and the amount of bentonite was replaced by 13 parts. The other parameters were the same as those in Example 3.
[0075] Comparative Example 2
[0076] The bentonite in Example 3 was omitted, and the amount of white carbon black was replaced by 13 parts. Other parameters were the same as those in Example 3.
[0077] The high water filling materials of Examples 1 to 4 and Comparative Examples 1 to 2 were cured under standard conditions for 28 days, and their compressive strength was tested. The compressive strength of the high water filling materials of Examples 1 to 4 and Comparative Examples 1 to 2 at 28 days was 25.3 MPa, 26.9 MPa, 32.8 MPa, 30.6 MPa, 26.6 MPa and 24.8 MPa, respectively. From the above data, it can be seen that the high water filling material provided by the present invention has excellent compressive strength, and the grading ratio of coal gangue has an effect on the compressive strength of the filling material; white carbon black and bentonite have a synergistic effect. At the same dosage, adding both can further improve the compressive strength of the filling material compared with adding them alone.
[0078] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A high-water filling material, comprising a cementitious material and water; the cementitious material comprises the following components in parts by weight: 10 parts of cement, 5-20 parts of fly ash, 20-40 parts of coal gangue, 0.1-0.5 parts of alkali activator, 1-10 parts of bentonite, 1-10 parts of white carbon black and 0.01-0.5 parts of admixture; the mass ratio of water to cementitious material is 2-15:
1.
2. The high water filling material according to claim 1, characterized in that: The coal gangue has continuous grading; the mass percentages of each grading are: 40-60% of 0-6mm coal gangue, 10-30% of 6-8mm coal gangue and 10-30% of 8-12mm coal gangue.
3. The high water filling material according to claim 1, characterized in that: The alkaline activator includes one or more of sodium hydroxide, potassium hydroxide, water glass and sodium aluminate.
4. The high water filling material according to claim 1, characterized in that: The admixture includes one or more of a retarder, a water reducing agent, a defoaming agent and a water retaining agent.
5. The high water filling material according to claim 1, characterized in that: The particle size of the fly ash is less than 45 μm.
6. The high water filling material according to claim 1, characterized in that: The particle size of the bentonite is less than 25 μm.
7. The high water filling material according to claim 1, characterized in that: The particle size of the white carbon black is 10 to 800 nm.
8. The high water filling material according to claim 1, characterized in that: The mass ratio of the water to the gelling material is 2 to 10:
1.
9. The method for preparing the high water filling material according to any one of claims 1 to 8, comprising the following steps: (1) mixing cement, fly ash, coal gangue, bentonite, white carbon black and an admixture to obtain a mixture; (2) mixing an alkali activator and water to obtain an alkali activator solution; (3) mixing the mixture obtained in step (1) and the alkaline activator solution obtained in step (2) to obtain a high water filling material; There is no order of precedence for steps (1) and (2).
10. Use of the high-water filling material according to any one of claims 1 to 8 or the high-water filling material prepared by the preparation method according to claim 9 in underground coal mines.
Citation Information
Cited By
Method for preparing underground cemented high-water-expansion filling material from negative carbon all-solid waste and application of underground cemented high-water-expansion filling material
CN121651840A